Increasing the Activity of Class VII.1 Students of SMP Negeri 9 Kendari at Indonesian Language Subjects Through the Application of Models STAD Type Cooperative Learning - Rachmawati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
The purpose of this study was to increase the activeness of class VII.1 students of SMP Negeri 9 Kendari in learning Indonesian by applying the STAD type cooperative learning model with the PAKEM approach. Class VII.1 of SMP Negeri 9 Kendari with 24 students. The study was carried out in the odd semester of the 2019/2020 school year. A teacher assists this classroom action research as an observer of both teacher and student activities. Action research is carried out in cycles, with the provision that if the first cycle has not achieved the expected goals, it will continue the process until the goals are achieved. The results of this study indicate that: (1) Ability reached the minimum criteria both in the first cycle from 70% and in the second cycle to 100% and the average aspect of the assessment from 82.0 to 86.2; (2) Aspects of student activity have reached the minimum criteria in the first cycle from 60% and in the second cycle to 90% and the average assessment from 79.6 to 86.4; and (3) In the first cycle, the number of active students as many as 11 people (45.83%), and in the second cycle increased to 23 people (95.83%). Using the STAD type cooperative learning model, the Indonesian language learning process can increase class VII.1 student of SMP Negeri 9 Kendari.